. 1. ( ) - Alexander Harin (Modern University for the Humanities, 2003)
. , - , , . – – These selected chapters of the textbook may give some acquaintance with an example of the teaching of accounting in Russia 10 years ago. The volume 1 of the textbook considers the foundations of the accounting theory.
Keywords: A2; I2; M41; 650; Accounting Theory; Higher education teaching; Russia